Retrospective, Observation Study: Quantitative and Qualitative Effect of Ezetimibe and HMG-CoA Reductase Inhibitors on LDL-Cholesterol: Are There Disappearance Thresholds for Small, Dense LDL and IDL? - Inoue, Ikuo; Awata, Takuya; Katayama, Shigehiro (Recent Patents on Cardiovascular Drug Discovery (Discontinued), 2010)
Lipid profiles were evaluated for 281 dyslipidemia patients treated with HMG-CoA reductase inhibitors (statins) for 2 years. The efficacy and safety of ezetimibe 10mg/day one-year add-on therapy were also retrospectively evaluated. The results show that in 281 dyslipidemia patients with a mean low-density lipoprotein-cholesterol (LDL-C) level of 120mg/dl or greater, ezetimibe 10mg/day administration reduced LDL-C levels to 90mg/dl or below. Patients who had been treated with one of six statins (pravastatin, simvastatin, fluvastatin, pitavastatin, atorvastatin, and rosuvastatin) for one year were given ezetimibe add-on therapy for one year, which reduced their LDL-C levels by 18% (pravastatin), 25% (simvastatin), 27% (fluvastatin), 30% (pitavastatin), 29% (atorvastatin), and 31% (rosuvastatin). Also, during the one-year add-on therapy, no severe adverse event was detected. An analysis of associations among lipids during a two-year lipid-lowering pharmacotherapy revealed correlations in a single patient. The correlation was between LDL-C and small, dense LDL as well as mid-band lipoprotein cholesterol. In conclusion, ezetimibe 10mg/day add-on therapy may be safe and effective for treating dislipidemia patients who have been treated with a statin. Moreover, this article discusses the disappearance thresholds for small, dense LDL and intermediate-density lipoprotein (IDL) by using the quantitative analysis of densitometric pattern based on genetic algorithm, which indicated that the major eight subspecies of lipoproteins (VLDL1, VLDL2, IDL1, IDL2, LDL1, LDL2, LDL3, HDL). The threshold for small, dense LDL indicates the IDL1 plus IDL2 plus LDL1 when LDL2 and LDL3 were not detectable, while the threshold for IDL indicates the LDL1 when IDL1, IDL2, LDL2 and LDL3 were not detectable.
Keywords: ezetimibe